Job Stress Is More Risky Causing Hypertension Compared To Smoking Habits In Private Workers In Cilacap, Indonesia - Budi Hernawan; Fajri Khoirul Annam (Universitas Muhammadiyah Purwokerto, 2023)
Hypertension is a rise systolic blood pressure above 140 mmHg and/or diastolic blood pressure above 90 mmHg. Hypertension is cause of cardiovascular morbidity mortality. In 2019, one billion people aged 30-79 with hypertension live in low-middle-income nations. Internal variables such heredity, age, race, stress, and gender create hypertension, whereas external ones such obesity, smoking habits, alcohol habits, and lack exercise cause hypertension. The study's goal was investigate which is more at risk of causing the incidence of hypertension events between job stress or smoking habits among employees in Cilacap Indonesia. The study employed an observational analytic cross-sectional design with primary data. Male machine operator who work at PT. Hasta Cipta Karya aged 18 to 64 years old were included. Purposive sampling was utilized, total 92 respondents. The survey discovered 49 (53.3%) severe stress, 55 (59.8%) smokers, and 57 (62.0%) hypertension Chi-square test results, correlation between job stress and hypertension p< 0.05, between the smoking habit and hypertension p< 0.05. The findings of the logistic regression test, job stress has an OR of 9.04 which is higher than smoking habits has an OR of 4.81. Job stress is more at risk of causing hypertension than smoking habits.